Silage Quality, Rumen Fermentation Characteristics, and Nutrient Digestibility of Sorghum bicolor cv. Samurai 1 Harvested at Different Maturity Stages Treated with Fibrolytic Enzyme - Ratnaningtyas, F. A.; Abdullah, L.; Kumalasari, N. R.; Ernawati, A.; Ridla, M.; Diapari, D.; Karti, P. D. M. H. (Tropical Animal Science Journal, 2025)
The Samurai 1 variety is a genetically mutated strain with superior agronomic characteristics and enhanced nutrient content. This study aimed to evaluate the effect of harvest maturity stages and fibrolytic enzyme (Sunsonzyme) treatment on the nutrient value, fermentative quality, and nutrient digestibility of Sorghum bicolor cv. Samurai 1 silage. The silage quality was assessed using a completely randomized design with a 3 x 3 factorial arrangement. Sorghum was harvested at three different maturity stages, namely 85, 90, and 95 days, with fibrolytic enzyme added at 0%, 0.025%, and 0.05% of the dry matter. In vitro fermentability and digestibility were evaluated using a randomized block factorial design, which was also based on the same three harvest stages and enzyme levels. Observed variables included the nutrient composition of the sorghum, physical characteristics and nutrient content of the silage, as well as in vitro fermentability and digestibility. The results showed a significant interaction between harvest maturity and enzyme level on lactic acid production and total volatile fatty acid (VFA). Harvest age significantly affected (p<0.05) all variables, while the treatment of fibrolytic enzyme significantly increased ammonia (NH₃) and total VFA concentrations, as well as reduced the fiber fraction of the silage (p<0.05). The harvest age of 90 days showed the best quality in terms of nutrients, silage, and rumen fermentability. The addition of enzyme levels up to 0.05% improved the fermentative quality of silage, reduced fiber fractions, and enhanced rumen fermentability.